THE CONSTITUTIONAL LAWSUIT IN IRAQI LEGISLATION - Amal Sani Muhamedameen (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Every organized political society living within the State has a constitution that includes clear and specific provisions regulating how to exercise powers, develop legislation and ensure rights, freedoms and limits that the authorities may not exceed in exercising their power. Therefore, the constitution represents the top of the legal pyramid in the state, and is not topped by any legal rules, and these rules should adhere to the framework of its provisions and not violate them, as the principle of the supremacy of the constitution and its superiority over all ordinary laws is one of the most important foundations on which the rule of law and institutions are based.